Survival of Spoilage and Pathogenic Microorganisms on Cardboard and Plastic Packaging Materials - Siroli, Lorenzo; Patrignani, Francesca; Serrazanetti, Diana I.; Chiavari, Cristiana; Benevelli, Marzia; Grazia, Luigi; Lanciotti, Rosalba (Frontiers in Microbiology, 2017)
The aim of this work was to study the interaction of corrugated and plastic materials with pathogenic and spoiling microorganisms frequently associated to fresh produce. The effect of the two packaging materials on the survival during the storage of microorganisms belonging to the species Escherichia coli, Listeria monocytogenes, Salmonella enteritidis, Saccharomyces cerevisiae, Lactobacillus plantarum, Pseudomonas fluorescens, and Aspergillus flavus was studied through traditional plate counting and scanning electron microscopy (SEM). The results obtained showed that cardboard materials, if correctly stored, reduced the potential of packaging to cross-contaminate food due to a faster viability loss by spoilage and pathogenic microorganisms compared to the plastic ones. In fact, the cell loads of the pathogenic species considered decreased over time independently on the inoculation level and packaging material used. However, the superficial viability losses were significantly faster in cardboard compared to plastic materials. The same behavior was observed for the spoilage microorganisms considered. The SEM microphotographs indicate that the reduction of superficial contamination on cardboard surfaces was due to the entrapping of the microbial cells within the fibers and the pores of this material. In addition, SEM data showed that the entrapped cells were subjected to more or less rapid lyses, depending on the species, due to the absence of water and nutrients, with the exception of molds. The latter spoilers were able to proliferate inside the cardboard fibers only when the absorption of water was not prevented during the storage. In conclusion, the findings of this work showed the reduction of cross-contamination potential of corrugated compared to plastic packaging materials used in fruit and vegetable sector. However, the findings outlined the importance of hygiene and low humidity during cardboard storage to prevent the mold growth on packaging.